Kontestasi pada Arsitektur Masjid Nusantara: Jelajah atas Masjid Ampel Surabaya dan Masjid Jami’ Malang - Gautama, Achmad Gat (UIN Maulana Malik Ibrahim Malang, 2010)
Conservation on architecture plays very important role in shaping the identity or memory of a place as well as presenting its current context. There are must be three strategies consisting in conservation, those are: continuity, development, and usage. Continuity shows the establishment on the tradition for the sake of the continuity on the building identity in the present and future time. Development is a process of changing and adjusting toward the current of a building to gain the best condition. Usage is creating the use or giving the facility for the existence sustainability of old, present, and future building. Through the tracing on two architecture cases, Masjid Sunan Ampel and Masjid Jami’ Malang, this paper aims to explore the character of architecture identity of mosque in Indonesia as an alternative of architecture sustainability which is relevant to Indonesian context, and to the development of technology as one of the instrument to build. The initial stage is exploring the architec of two mosques by using three conservation strategies as the reading tool. The next stage is doing an interpretaive analysis by comparing the finding character identity both mosques’ identity in dialogic way. The above study presents the two character of Indonesain mosques’ architecture which includes technology in the building process. These characters have been becoming the starting planning strategy of mosque’s architecture which orientates to Indonesian context as well as creatively and innovatively. Konservasi pada arsitektur memainkan peran yang sangat penting dalam membentuk identitas atau memori suatu tempat sekaligus menyajikan konteksnya saat ini. Harus ada tiga strategi yang terdiri dalam konservasi, yaitu: kontinuitas, pengembangan, dan penggunaan. Kontinuitas menunjukkan kemunculan tradisi demi kelangsungan identitas bangunan di masa sekarang dan masa depan. Pembangunan adalah proses perubahan dan penyesuaian terhadap arus bangunan untuk mendapatkan kondisi terbaik. Penggunaannya menciptakan penggunaan fasilitas untuk keberlanjutan bangunan lama, sekarang dan masa depan. Melalui penelusuran dua kasus arsitektur, Masjid Sunan Ampel dan Masjid Jami 'Malang, makalah ini bertujuan untuk mengeksplorasi karakter identitas arsitektur masjid di Indonesia sebagai alternatif keberlanjutan arsitektur yang sesuai dengan konteks Indonesia, dan perkembangan teknologi. sebagai salah satu alat untuk membangun. Tahap awalnya yaitu mengeksplorasi arsitektur dua masjid dengan menggunakan tiga strategi konservasi sebagai wacana. Tahap selanjutnya adalah melakukan analisis interpretatif dengan membandingkan identitas karakter temuan kedua identitas masjid tersebut secara dialogis. Studi di atas menyajikan dua karakter arsitektur masjid Indonesia yang mencakup teknologi dalam proses pembangunan. Hal ini telah menjadi strategi perencanaan awal arsitektur masjid yang berorientasi pada konteks Indonesia serta kreatif dan inovatif.